Atención psicológica en el cáncer infantil - Méndez, Xavier; Orgilés, Mireia; López-roig, Sofía; Espada, José Pedro (Psicooncología, 2004)
The aim of this paper is to examine the psychological repercussions of cancer in children and the main interventions that psychologists can apply to the oncologic patient during the diagnosis, the course of the illness and the medical treatment. The most effective psychological techniques to reduce the symptoms of cancer and the side effects of the treatment, like anticipatory nausea and vomiting, pain, fatigue or tiredness, are reviewed. Besides, the interventions to reduce or avoid anxiety and depression in children who have cancer and some instructions to improve the adherence to the medical treatment are presented. Finally, some suggestions are provided to get the pediatric cancer survivor have a properly quality of life and some ideas to support and assist the family in case the patient dies.
Keywords: Cancer; Childhood; Psychological intervention